Salicylic acid seed priming instigates defense mechanism by inducing PR-Proteins in Solanum melongena L. upon infection with Verticillium dahliae Kleb - Mahesh, H M (Plant physiology and biochemistry : PPB, 2017)
Copyright © 2017 Elsevier Masson SAS. All rights reserved.